(untitled) (The Review of Diabetic Studies, 2024)
Background: Saudi Arabia is advancing in the field of healthcare at a rapid pace and patient safety culture is the integral part of the same. Patient safety culture (PSC) coincides with strategic aims of Saudi Vision 2030, which advances healthcare reform agenda in the nation. This review study will provide information for national policy-makers, hospital directors, and educators for potential strategies to develop interventions that would advance nursing leadership in safety, and to align hospital practices with national policy related to safety and also advances in global practices. Study Objectives: The main objective of the study is to review existing studies on patient safety culture in Saudi hospitals from the nursing perspective. The study will also focus on the identification of key themes, barriers, and facilitators influencing PSC. Materials and Methods: Study is a narrative based review study and uses exploratory research design where the data is gathered from various sources on the basis of pre decieded criteria of inclusion and exclusion. PRISMA is used to segregate and screen the collected studies. The results are presented in the form of results and discussion, in a frame of chronology for better understanding. Results: Nurses have recognized that safety practices are vital, in spite of hurdles such as lack of support from hospital management, inadequate nurse-patient ratios, and worries about punitive action. Other barriers include cultural differences, ineffective communication, and inconsistent training.